O direito de ser si mesmo: a identidade pessoal na ordem constitucional brasileira - Dias, Eliza Cristina Gonçalves (2015)
What makes up the human being at his substance, what makes him unique, different from the others, only identical to himself, is a question that arouses the curiosity of the most varied branches of science, from Philosophy to Medicine. The legal science, distinctly, turned his concern to analysis and tutelage existential questions related to human person, modernly. After the Second World War, the atrocities afflicted by the German Nazi regime had repercussions worldwide, especially in European countries, and realized themselves to the need for a Right that tutelasse the human being in his dignity, regardless of any other determinant, simply because it exists. The constitutional law was the gateway of this ideology of the human being protection through the fundamental rights. The civil law, following the constitutions, developed a category of rights entitled the rights of personality, in which the human being and his personal attributes are protected as subjective rights. In this dynamic of greater protection of the human being, the Italian courts developed the right to personal identity. This right includes some other personality rights as its integral elements, which together represent the synthetic and global formula of social representation of human beings, their ideas, their moral and ideological heritage and their personal identifiers such as name, image and personal data. In this paper analyzes the right to personal identity as a right of personality, similar to that developed by the doctrine and Italian courts; examines whether the absence of legal provision and jurisprudence development on the issue generate an obstacle to the protection of individual identity in the Brazilian law. And it will be examined whether the 1988 Federal Constitution, as his regime values and principles would have the ability to protect the personal identity, a dimension of the free development protection of individual subjectivity, ie the free development of personality and choice life of every human being. Even analyzes if the Federal Constitution of 1988, before its regime of values and principles, would have the ability to protect the personal identity in a dimension of the free development of individual subjectivity, i.e. the free development of personality and respect to the choice of the individual project of life. The methodology used in this work is the bibliographical legislation and case law research, in the works of some foreign authors, attempting to promote construction of the right to personal identity. It can be possible, at the end, conclude that the Brazilian law has tools for identity protection in its entirety, either by protection of elements that compose it, whether through the use of general clause protection of human dignity.